The Misfortunes and Return of Briton Hammon (1747- 1760): Introduction and Translation - Peña, Beatriz Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Considered the first autobiographical account of an Afrodescendant slave published in America, A Narrative of the Uncommon Sufferings, and Surprizing Deliverance of Briton Hammon, a Negro Man (Boston 1760) has not yet been translated into Spanish. This work, encompassing shipwreck, Native American captivity, slavery in Cuba, and slavery in Massachusetts, is of interest to Spanish-speaking scholars not only for its foundational character but also because Havana is a key location in Briton Hammon's captivity story. The text reflects the tense relationship between the Hispanic Caribbean and the British colonies in America in the 18th century. The following pages offer a translation and an introductory study of the same.